2020
DOI: 10.1155/2020/8810553
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parboiling Conditions on Physical and Cooking Quality of Selected Rice Varieties

Abstract: Most locally cultivated rice varieties in Ethiopia have low physical (low head rice yield, high broken rice yield, and high percentage of chalkiness) and cooking qualities (low water uptake ratio and swelling ratio). Parboiling, a process which involves soaking, steaming, and drying, has been identified as a key technique to improve cooking and milling quality of rice. The current study is aimed at elucidating the effect of parboiling on physical and cooking qualities of three rice varieties (Gumara, Edget, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
(20 reference statements)
0
6
2
Order By: Relevance
“…The results showed that the cooking time increased as the soaking temperature and soaking time were increased. The found results in contrast with Meresa et al ( 2020 ) studied that the minimum cooking times of Ethiopian rice varieties were identified as 16–23 min for Ediget and 16–23 min for Gumara rice varieties when soaked at 40–80°C for 10–50 min. The variation in cooking time might be due to differences in genetic makeup and microwave‐assisted parboiling equipment which are significantly decreased the cooking time of the rice grains (Rockembach et al, 2019 ).…”
Section: Resultscontrasting
confidence: 63%
See 3 more Smart Citations
“…The results showed that the cooking time increased as the soaking temperature and soaking time were increased. The found results in contrast with Meresa et al ( 2020 ) studied that the minimum cooking times of Ethiopian rice varieties were identified as 16–23 min for Ediget and 16–23 min for Gumara rice varieties when soaked at 40–80°C for 10–50 min. The variation in cooking time might be due to differences in genetic makeup and microwave‐assisted parboiling equipment which are significantly decreased the cooking time of the rice grains (Rockembach et al, 2019 ).…”
Section: Resultscontrasting
confidence: 63%
“…The results showed that the cooking time increased as the soaking temperature and soaking time were increased. The found results in contrast with Meresa et al (2020)…”
Section: Cooking Timecontrasting
confidence: 72%
See 2 more Smart Citations
“…The chalk percentage ranged from 0 percent to 89.56 percent, with an average of 12.56 percent. The large variability is partially explain by the fact that our samples include parboiled rice, which has a low chalk rate as the parboiling process decreases chalkiness [36]. The average chalk rate of the samples corresponds to sub-standard rice according to the Bangladesh standard [29].…”
Section: Plos Onementioning
confidence: 99%